2011
DOI: 10.1089/vbz.2010.0232
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Study of Intestinal Parasites of Dogs from Yucatan, Mexico, and Their Risk to Public Health

Abstract: The prevalence of intestinal parasites in dogs and factors associated were studied in a rural community of Yucatan (southern Mexico), with special attention to those gastrointestinal parasites potentially transmitted to man. One hundred thirty dogs from 91 households were studied. Fecal samples were processed by the centrifugation-flotation and the McMaster techniques. To determine factors associated with zoonotic parasites in dogs, univariate analysis was performed, using sex, age, and body condition as indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 21 publications
2
22
1
14
Order By: Relevance
“…These actions could explain the lower prevalence and intensity of infection reported at this time categorized between low and medium intensity of infection. In the specific case of T. canis , a higher prevalence (12.5%) was found compared to previous studies in the same area where 6.2% was found [ 15 ]. T. canis mainly affects puppies with frequently fatal consequences.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…These actions could explain the lower prevalence and intensity of infection reported at this time categorized between low and medium intensity of infection. In the specific case of T. canis , a higher prevalence (12.5%) was found compared to previous studies in the same area where 6.2% was found [ 15 ]. T. canis mainly affects puppies with frequently fatal consequences.…”
Section: Discussioncontrasting
confidence: 67%
“…The high variation observed has been associated with various weather conditions, idiosyncrasies, and sanitary control of dogs. A previous study in the same community was performed four years ago and prevalence of gastrointestinal parasites in dogs was 80% with a high egg output of A. caninum , T. canis , and T. vulpis found; in this study, deworming of dogs was performed and talks to children, adolescents, and adults about health management of dogs were given [ 15 ]. These actions could explain the lower prevalence and intensity of infection reported at this time categorized between low and medium intensity of infection.…”
Section: Discussionmentioning
confidence: 99%
“…This similarity could possibly be attributed to high population density (Uehlinger et al, 2013) and the exposure of stray and owned dogs to common factors including poor hygiene, lack of access to clean water, or environmental contamination (Campbell et al, 2016). Previous studies have demonstrated that soil contamination in gardens and public grounds by infectious parasites significantly increases the risk of infection (Rodríguez-Vivas, 2011). Giardia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Hair condition (P=0.11, P=0.88, OR=1.1) and body condition (P=0.49, P=0.66, OR=1.2) were not significantly associated with prevalence of Giardia spp. infection, despite the known negative effects that parasites, in general, have over canine nutrition (Hiepe et al, 2011) and the results in other studies in which poor body condition of dogs was associated with a higher prevalence of intestinal zoonotic parasites and a higher risk of infection (Rodríguez-Vivas, 2011).…”
Section: Variablementioning
confidence: 91%
“…EPG of faeces were obtained by multiplying the number of eggs by a factor of 50 [29]. In order to quantify levels of infection, EPG of faeces were categorised into three groups: low (50-100), moderate (150-500) and high (≥ 550) [35]. The analysis of faecal samples resulted into a binary response variable that indicated whether a sampled dog was infected or not infected.…”
Section: Data Collectionmentioning
confidence: 99%